قواعد المصلحة في السياسة الشرعية عند الامام القرافي - بن عطية، محمد (University of Eloued جامعة الوادي, 2024)
يهدف هذا البحث إلى بيان قواعد المصلحة في السياسة الشرعية عند الإمام القرافي، من حيث المفهوم، والتأصيل، وأنواع المصلحة، مع إيراد بعض تطبيقاتها, من خلال المنهج الاستقرائي، والمنهج التوثيقي. ومن أبرز ما توصلنا إليه من خلال هذا البحث, أن العمل بالسياسة الشرعية لا يأتي كيفما اتفق، بل يقوم على أصول وقواعد شرعية، وينضبط بضوابط معينة، وأن أحكامها متغيرة تبعاً لتغيّر المصالح والمقاصد الشرعية المرعية عند اتخاذها على الرعية لتدبير شؤونهم ورعاية مصالحهم، دينياً ودنيوياً.This research aims to explain the rules of interest in Sharia politics according to Imam Al-Qarafi, in terms of concept, rooting, and types of interest, while presenting some of its applications, through the inductive approach and the documentary approach. One of the most prominent findings that we have achieved through this research is that the work of Sharia policy does not come as agreed upon, but rather is based on Sharia principles and rules, and is governed by certain controls, and that its rulings are variable according to the change in the legitimate interests and objectives taken into account when it is taken over the subjects to manage their affairs and take care of their interests, of religion and life.
Keywords: قواعد المصلحة; القرافي; السياسة الشرعية; Sharia policy; rules of interest; Al-Qaraf